PENGARUH MODEL PEMBELAJARAN KOOPERATIF BERKIRIM SALAM DAN SOAL TERHADAP MOTIVASI BELAJAR PPKN SISWA KELAS VIII SMP DWI SEJAHTERA PEKANBARU - Irmalini Syafrita; Gimin '; Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this Pelelitian by low motivation to learn PPKn DwiSejahtera junior high school students in Pekanbaru. Formulation of the problem in thisresearch is: "Is There Influence Learning Model send greetings and Motivation StudyQuestions PPKn of Students Grade VIIIat SMP Dwi Sejahter Pekanbaru?".This researchaimed to Know Influence of Cooperative Learning Model Problem send greetings andMotivation Study PPKn of Students Grade VIIIat SMP Dwi Sejahtera Pekanbaru ". Thisresearch was conducted in SMP Dwi Sejahtera Pekanbaru ". This research wasconducted at SMP Dwi Sejahtera Pekanbaru on February 2016. This reseach is aquantitative descriptive the population in this research is class VIII of SMP DwiSejahtera Pekanbaru. The sample in this study were drawn based on the technique of"Randem". Where classes were taken as the sample in this study were students of classVIII 2 (Class Experiment) and VIII Class 3 (Class controls) were the students who weregiven conventional methods of data later analysis using homogeneity test and test "t".The subject matter is applied to the model of exchanging greetings and the matter ismaterial PPKn CHAPTER VIII class II "various constitutions in force in Indonesia" and"deviations against the current constitution diIndonesia". HSIL based research showsthat there are significant learning motivation among students who use learning modelssend greetings and Problem and the conventional method in junior Dwi SejahteraPekanbaru (T_ (count) = 38.18> t_tabel = 1.997). Where there average increasemotivation to learn PPKn experimental class of 18.94 into 26.42, and the averageincrease motivation to learn PPKn control classes from 19.88 into 24.14. Thus thehypothesis there is the effect of using learning model send greetings and Problem onmotivation to learn PPKn eighth grade students of SMP Dwi Sejahtera Pekanbaru,accepted.Keyword: sent greetings and Problems, Motivation, Civics Lesson2